Helium impurity transport on grain boundaries: Enhanced or inhibited?. (17th June 2015) - Hammond, Karl D.; Hu, Lin; Maroudas, Dimitrios; Wirth, Brian D.
Abstract: We present atomistic simulations that show that transport of helium is inhibited on grain boundaries in tungsten. This finding is contrary to self-diffusion, or diffusion of substitutional impurities in metals, for which transport is generally enhanced along grain boundaries, but is similar to the behavior observed for hydrogen in past studies on low-angle grain boundaries, for which transport also occurs via interstitial diffusion. In the case of helium transport in tungsten, diffusion is biased toward grain boundaries, but once a helium atom or group of atoms is on a grain boundary, diffusion is impeded rather than enhanced. The reduced rate of diffusion on grain boundaries produces a higher concentration of helium in the grain boundary regions. The effect arises from the relative insolubility of helium inmost materials combined with the size mismatch between helium and tungsten, which results in an interstitial diffusion mechanism rather than diffusion that relies on the presence of self-vacancies. In light of this, it is important to note that grain boundaries will not facilitate transport of helium in tungsten and other metals, but in fact that helium is immobilized on grain boundaries.